Tanggung jawab lembaga keuangan terhadap pinjam nama menurut pasal 1873 KUH perdata - Assail, Muhammad Alaik; Hasan, Akhmad Farroh (Maliki Interdisciplinary Journal, 2025)
Economic problems faced by society, such as the imbalance between income and living needs, often lead individuals to engage in borrowing or debt transactions. This practice is common, both individually and through formal financial institutions such as cooperatives and banks. However, the phenomenon of "nominee borrowing" or the use of another person's identity in financing agreements has increasingly emerged, raising legal concerns. Nominee agreements are often used to bypass legal provisions or administrative requirements of financial institutions. Under civil law, Article 1873 of the Indonesian Civil Code (KUHPerdata) stipulates that a private deed can have the same evidentiary power as an authentic deed if acknowledged or legalized. Nevertheless, legal issues arise regarding who bears responsibility in agreements involving false identities—whether it is the identity owner, the user of the identity, or the financial institution granting the financing. This study aims to examine the responsibility of financial institutions, particularly KSPPS Tunas Artha Mandiri, in the practice of nominee borrowing, and to assess the extent to which these institutions can be held accountable for legal consequences arising from agreements involving borrowed or falsified identities, based on Article 1873 of the Indonesian Civil Code.